Afghan Women's Barriers to Seeking Help for Domestic Violence in Australia. Issue 2 (3rd April 2023) - Afrouz, Rojan; Crisp, Beth R.; Taket, Ann
ABSTRACT: Help seeking for domestic violence is complex and multifaceted, and settling in a new country might make the help-seeking process more challenging and complicated. This study explored the barriers to seeking help for domestic violence, specifically experienced by Afghan women after settling in Australia. The study involved 21 semistructured interviews with newly arrived Afghan women. Interviews were audio recorded and transcribed, and the data were analysed thematically. The barriers Afghan women experienced were embodied in cultural norms to stay in marital relationships, demands to preserve the family's reputation, personal circumstances, and women's experiences with, and perspectives on, available services. The findings suggest that policy and practice should recognise those barriers and respond to them in a culturally appropriate way. IMPLICATIONS Domestic violence services' procedures and processes should be developed based on an understanding of multiple layers of oppression and barriers to seeking help for migrant women. Service providers should apply an intersectional lens along with antioppressive perspectives to address barriers to domestic violence services women experience at different levels. Social workers in domestic violence services need relevant training to provide culturally appropriate services to migrant women.